Urban sprawl literature review: definition and driving force - Yasin, Muhammad Yazrin; Mohd Yusoff, Mariney; Abdullah, Jamalunlaili; Mohd Noor, Nisfariza; Hj. Mohd. Noor, Norzailawati (Department of Geography, UKM, 2021)
The concept of urban sprawl spans multiple dimensions indicating how urban built-up land cover adds up throughout exurban landscapes. These different dimensions of urban sprawl require a re-examination of definitions and their driving forces because certain policies were formulated from the proposition of informed knowledge and have implicitly gratified urban sprawl into adjoining urban peripheries. This article aimed to offer an alternative perspective on urban sprawl, contributing to a better comprehension of its definition and driving forces. The revision of urban sprawl definitions into six categories have been done based on their repercussion, unaesthetic design, driving force, undesirable pattern, extended character, and their consequences to the environment, to assist in giving an in-depth understanding of urban sprawl in order to implicate effective policy actions. A revision of the driving forces of urban sprawl into various socioeconomic, institutional, demographic, market and technological factors further support the research on spatial planning and urban growth. It is conducted through a detailed discussion and analysis of evidence retrieved from wide-ranging urban studies literature. An informed decision through understanding the driving force of urban sprawl and addressing the root cause can produce a twofold benefit of socio-environment wellbeing and growth-friendly policy initiatives.